Student competency development in MSIB internship at SEAMEO QITEP language library - Azizah Hafshah Hafsari; Rizki Rachman (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Internship is an activity conducted by students to improve the soft skills they possess. Currently, many internship programs are organized, one of which is the Merdeka Belajar Kampus Merdeka program, held directly by the Minister of Education and Culture. In its implementation, internship serves as a starting point for students before entering the real world of work. Therefore, the place or institution where the internship is carried out is highly considered, as it should align with the student's field of study. The purpose of this article is to describe the tasks that internship students must perform at SEAMEO QITEP in Language and whether the internship program plays an important role in improving student competencies. The method used is descriptive qualitative with a case study approach. The data used is obtained from internship reports and tends to use analysis of SEAMEO QITEP in Language regarding the connection between internships and the competencies possessed by students. The results obtained indicate that the MBKM MSIB internship program enables students to sharpen their skills and abilities in their field. The competencies gained include how to manage a specialized library effectively and how to conduct digital library activities. Additionally, students have become proficient in preparing administrative letters required by partners for various activities.   Abstrak Magang merupakan kegiatan yang dilakukan oleh mahasiswa untuk meningkatkan kompetensi softskill yang dimilikinya. Program magang saat ini sudah banyak diselenggarakan salah satunya yaitu program MBKM yang diselenggarakan langsung oleh Menteri Pendidikan dan Kebudayaan. Dalam implementasinya, magang merupakan sebuah awalan bagi mahasiswa sebelum terjun di dunia kerja yang sesungguhnya. Oleh karena itu, tempat yang digunakan oleh mahasiswa perlu diperhatikan dan sesuai dengan bidang keilmuan yang dijenjanginya. Tujuan penulisan artikel ini yaitu apa saja uraian tugas yang harus dikerjakan oleh mahasiswa magang di SEAMEO QITEP in Language, dan apakah program magang yang dilakukan oleh mahasiswa dapat berperan penting dalam peningkatan kompetensi mahasiswa. Metode yang digunakan yaitu deskriptif kualitatif dengan pendekatan studi kasus. Data yang digunakan diperoleh dari hasil laporan magang dan cenderung menggunakan analisis terhadap SEAQIL tentang keterkaitan magang dengan kompetensi yang dimiliki mahasiswa. Mahasiswa magang memperoleh pengalaman praktis dalam pengelolaan sumber daya manusia, pengelolaan perpustakaan, dan administrasi umum. Kompetensi yang dikembangkan meliputi kemampuan komunikasi, manajemen, kolaborasi, serta pengelolaan informasi yang berdampak positif pada pengembangan soft skill dan hard skill, seperti berpikir kritis, pemecahan masalah, dan kreativitas. Selain itu, perpustakaan SEAQIL berperan penting dalam mendukung pengembangan SDM melalui koleksi bahan pustaka dan pengelolaan perpustakaan digital. Kata Kunci: kompetensi; magang; Magang dan Studi Independen Bersertifikat; MSIB